Providers' time spent and tools used when discussing the HPV vaccine with parents of adolescents. Issue 50 (7th December 2016) - Dempsey, Amanda F.; Lockhart, Steven; Campagna, Elizabeth J.; Pyrzanowski, Jennifer; Barnard, Juliana; O' Leary, Sean T .
Highlights: Communication tools about HPV vaccines are not widely used by providers. When current tools are used, vaccine discussion times tend to be longer. Better communication tools for provider HPV vaccines discussion are needed. Abstract: Objectives: Little is known about HPV vaccine communication tools currently used by primary care providers of adolescents, or how such tools impact the quality of HPV vaccine recommendations, which some have defined as using a "presumptive" communication style, continuing to offer vaccines despite resistance, and strongly recommending vaccines at the appropriate ages. We surveyed primary care providers to assess their current use of HPV vaccine communication tools, and how these related to their HPV vaccine recommendation quality. Study Design: Cross sectional survey of 183 pediatrics and family medicine primary care providers in the Denver metro area. Results: Response rate was 82% (n = 150). Most (59%) providers used a presumptive vaccine recommendation >75% of the time, and 76% reported continuing to offer the HPV vaccine even after parent refusal. However, less than two-thirds of providers "strongly" recommended the vaccine to 11–12 year olds (60% for females, 55% for males, p = 0.02). The HPV vaccine information sheet from the Centers from Disease Control and Prevention was the most frequently used communication tool during clinical visits (64% used at least 75% of the time) and directing parents to preferred websites was the most frequently used between-visit communication tool (21% used >50% of visits). Use of tools was not associated with any measure of HPV vaccine recommendation quality but was associated with longer HPV vaccine discussion times. Conclusions: Providers use only limited types of adolescent HPV vaccine communication tools, and frequently do not use preferred vaccine communication strategies. Better engagement with existing HPV vaccine communication tools, and/or the creation of new tools may be needed to enhance providers' ability to provide high quality HPV vaccine recommendations.